Nimbus. Повесть о докторе Гаазе - Нежный Александр (Центр книги Рудомино, 2013)
Экземпляры: (20141009) / Инвентарный номер: 38115 / Цена: 220.00 / Сис.шифр: Р2 / Авт.знак: Н 43 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6